Rapid Diagnostic Platform for Colorimetric Differential Detection of Dengue and Chikungunya Viral Infections. - Wang,R; Ongagna-Yhombi,SY; Lu,Z; Centeno-Tablante,E; Colt,S; Cao,X; Ren,Y; Cárdenas,WB; Mehta,S; Erickson,D (Anal Chem, 2019)
In this work, we demonstrate a rapid diagnostic platform with potential to transform clinical diagnosis of acute febrile illnesses in resource-limited settings. Acute febrile illnesses such as dengue and chikungunya, which pose high burdens of disease in tropical regions, share many nonspecific symptoms and are difficult to diagnose based on clinical history alone in the absence of accessible laboratory diagnostics. Through a unique color-mixing encoding and readout strategy, our platform enabled consistent and accurate multiplexed detection of dengue and chikungunya IgM/IgG antibodies in human clinical samples within 30 min. Our multiplex assay offers several advantages over conventional rapid diagnostic tests deployed in resource-limited settings, including a low sample volume requirement and the ability to concurrently detect four analytes. Our platform is a step toward multiplexed diagnostics that will be transformative for disease management in resource-limited settings by enabling informed treatment decisions through accessible evidence-based diagnosis.